Paediatric primary cutaneous marginal zone B‐cell lymphoma: does it differ from its adult counterpart?. (20th February 2017) - Amitay‐Laish, I.; Tavallaee, M.; Kim, J.; Hoppe, R.T.; Million, L.; Feinmesser, M.; Fenig, E.; Wolfe, M.E.L.; Hodak, E.; Kim, Y.H.
Summary: Background: Primary cutaneous marginal zone B‐cell lymphoma (PCMZL) has rarely been reported in patients younger than 20 years. Objectives: To report our experience with PCMZL in the paediatric/adolescent age group. Methods: Medical records of patients diagnosed with PCMZL before age 20 years and managed at two cutaneous lymphoma clinics in the U.S.A. and Israel from 1992 to 2015 were reviewed. Results: The study group included 11 patients (six girls; median age 16 years, range 6–19·5); 10 had generalized/multifocal (T3) and one had regional/localized (T2) disease. Lesions were located on the limbs in all patients and the trunk in six; two had facial lesions. Staging in all but one was based on whole‐body computed tomography or positron emission tomography. Initial management in most patients included nonradiation modalities: one patient with localized disease received intralesional steroids; six patients with multifocal disease received the following: topical/intralesional steroids ( n = 3); excision ( n = 2); 'watch and wait' ( n = 1). No extracutaneous progression was noted during a median follow‐up of 5·5 years (mean 7·5, range 0·5–14). At present, five patients are in complete remission. Conclusions: Based on our data (largest series in the literature with the longest follow‐up), the clinicopathological presentation and course of PCMZL in the paediatric/adolescent age group are similar to those in adults. Given the indolent course and the long life expectancy of these young patients, the cumulative risk of imaging studies and the age‐related potential toxicity of treatment, especially radiation, should be taken into consideration. Abstract : What's already known about this topic? Primary cutaneous marginal zone B‐cell lymphoma (PCMZL) rarely occurs in the paediatric/adolescent age group. The presentation and prognosis appear to be similar to adult PCMZL. Data on optimal staging and management in younger patients are lacking. What does this study add? Largest series of PCMZL in patients aged < 20 years, with the longest follow‐up. Paediatric PCMZL is similar to adult PCMZL in terms of clinical features, histopathology, molecular findings and prognosis. The use of computed tomography (CT)/positron‐emission tomography–CT in this age group needs to be further evaluated to minimize any unnecessary radiation exposure. Radiotherapy should be used with greater caution in children/adolescents, starting with the lowest possible dose. Linked Comment:Kempf. Br J Dermatol 2017;176 :857–858 Plain language summary available online